2005
DOI: 10.2754/avb200574030347
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Cleome droserifolia Aerial Parts: Lipid Peroxidation-Induced Oxidative Stress in Diabetic Rats

Abstract: The present study aims to investigate the antidiabetic as well as the effect on lipid peroxidation of three different doses (50, 100, and 200 mg/kg) of Cleome droserifolia aerial parts methanolic extract in comparison with glibenclamide in alloxan-induced diabetic rats.Forty-two rats (35 diabetic and 7 normal) were included in this study. Oral administration of 100 and 200 mg/kg of the methanolic extract for 3 weeks significantly (P < 0.05) restored the blood glucose level, plasma malondialdehyde and urine sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…In the present study, STZ-induced diabetic pregnant mice (GII) showed a significant increase in glucose level as compared to the control group. These results are in agreement with those of many authors using STZ-diabetic animals (El-Naggar et al 2005;Hassan et al 2008;Helmy et al 2007). Gojo et al (2007) concluded that diabetes can be produced in animals by i.p.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, STZ-induced diabetic pregnant mice (GII) showed a significant increase in glucose level as compared to the control group. These results are in agreement with those of many authors using STZ-diabetic animals (El-Naggar et al 2005;Hassan et al 2008;Helmy et al 2007). Gojo et al (2007) concluded that diabetes can be produced in animals by i.p.…”
Section: Discussionsupporting
confidence: 83%
“…The use of traditional medicine and medicinal plants in most developing countries for the maintenance of good health has been widely observed [3][4]10]. Free radical-induced lipid peroxidation has been associated with a number of disease processes including oxidative stress [11].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, research efforts are currently focusing on the protective biochemical complement of naturally occurring plant phytochemicals which have antioxidant activity. These phytochemicals (vitamins, proteins, enzymes, carotenoids, flavonoids, anthocyanins, phenolic compounds and pectin) vary in composition and mechanism of action in protecting tissues against oxidative damage [4].…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals are formed disproportionately in diabetes by glucose oxidation, nonenzymatic glycation of proteins and the subsequent oxidative degradation of glycated proteins (2). Abnormally high level of free radicals and the simultaneous decline in antioxidant defense mechanisms may lead to the damage of cellular organelles and enzymes, increased lipid peroxidation and development of insulin resistance (3). Current drugs used for the treatment of diabetes are associated with several side effects and hence there is need for effective, safe and better oral hypoglycemic agents (4).…”
Section: Introductionmentioning
confidence: 99%